The relationship between communication and education through the creative personality of the teacher - Navickienė, Vida; Sederevičiūtė-Pačiauskienė, Živilė; Valantinaitė, Ilona; Žilinskaitė-Vytienė, Viktorija (Creativity Studies, 2019)
The article focuses on the relationships of communication and educational processes, creativity aspects in the context of higher education. A creative personality of the teacher determines how smooth and efficient these relationships are. The results of the quantitative research (sample – 124 teachers) conducted at Lithuanian higher education institutions and coprehensively presented in the article reveal the attitude of Lithuanian higher education teachers towards the significance of communication in the educational process. Though higher education teachers have to possess various competences such as personal, communication, social, lifelong learning, methodological, planning, organisational, leadership and assessment ones, the respondents distinguished several most significant to them. The research revealed that teachers see personal and communication competences as the most important ones, which also reveal and substantiate close relationships of communication and educational processes. The relationship is enhanced by a creative personality of the teacher, his or her positive personal qualities and values. Higher education teachers not only perceive the significance of communication and educational competences in the educational process but also express a need for their continuous improvement.Article in English.Komunikacijos ir edukacijos santykis per kūrybišką dėstytojo asmenybęSantraukaStraipsnyje analizuojamos komunikacinių ir edukacinių procesų sąsajos aukštojo mokslo kontekste. Išsamiai pristatomi kiekybinio tyrimo, kuriame buvo naudoti ir atviri apklausos klausimai, rezultatai, rodantys Lietuvos aukštųjų mokyklų dėstytojų požiūrį į komunikacijos svarbą edukaciniame procese. Nors dėstytojai turėtų būti išsiugdę įvairias kompetencijas: asmeninę, komunikacinę, socialinę, nuolatinio mokymosi, metodinę, planavimo, organizavimo, vadovavimo, vertinimo, tačiau jie išskyrė tik keletą jų kaip svarbiausių. Tyrimas parodė, kad dėstytojams svarbiausios yra trys kompetencijos – asmeninė, komunikacinė ir nuolatinio mokymosi, kurios atskleidžia ir pagrindžia glaudžias komunikacijos ir edukacijos procesų sąsajas. Dėstytojai ne tik suvokia komunikacinės ir edukologinės kompetencijų svarbą edukaciniame procese, bet ir išreiškia poreikį jas nuolat tobulinti. Analizuojant teorinius ir tyrimo metu gautus rezultatus, teigtina, kad edukaciniame procese yra tiesioginis komunikacinės ir edukologinės kompetencijų ryšys.Reikšminiai žodžiai: komunikacinės kompetencijos, kūrybiškas dėstytojas, edukacinės kompetencijos, aukštasis išsilavinimas, dėstytojo komunikacija.